Evolution of mimicry patterns in Metriorrhynchus (Coleoptera: Lycidae): the history of dispersal and speciation in southeast Asia - Bocak, Ladislav; Yagi, Takashi (Evolution; international journal of organic evolution, 2010)
The concept of Müllerian mimicry suggests convergent evolution to an intermediate pattern and does not predict polymorphism in mimicry rings. We examined the evolution of mimicry patterns and the order of divergence of various factors, including the role of aposematic patterns in speciation, in a clade of net-winged beetles with a robust phylogeny that suggests that they dispersed from the Australian to Asian plate. We found strong evidence for the evolution of mimicry via advergence in Metriorrhynchus because older patterns are represented in the Oriental region within more than 100 species of lycids from several lineages. Advergence was likely the cause of the observed intraspecific polymorphism in contrast to the predicted universal monomorphism. Polymorphism was found in populations of two species in Sumatra and Borneo and in populations fine-tuned to subtle variants in various habitats. The advergence is likely to be based on the small population sizes of immigrants. The differences in population sizes result in much higher benefits for dispersing species than native populations. Speciation was trigged by the divergence in aposematic coloration, and the genetic differences accumulated slowly during incomplete isolation. We assumed that the differentiation in genitalia through sexual selection ultimately reinforced speciation initiated by the shift between mimicry patterns.
Keywords: Polymerase Chain Reaction; Asia, Southeastern; brouci; jihovýchodní Asie; Coleoptera; Biological Evolution; Animals; Phylogeny; zvířata; fylogeneze; biologická evoluce; polymerázová řetězová reakce